A transdisciplinary collaborative journey leading to sensorial clothing. Issue 4 (1st October 2020) - Kuusk, Kristi; Tajadura-Jiménez, Ana; Väljamäe, Aleksander
ABSTRACT: Recent science funding initiatives have enabled participants from a diverse array of disciplines to engage in common spaces for developing solutions for new wearables. These initiatives include collaborations between the arts and sciences, fields which have traditionally contributed very different forms of knowledge, methodology, and results. However, many such collaborations often turn out as science communication and dissemination activities that make no concrete contribution to technological innovation. Magic Lining, a transdisciplinary collaborative project involving artistic and scientific partners working in the fields of e-textile design, cognitive neuroscience and human-computer interaction, creates a shared experiential knowledge space. This article focuses on the research question of how a transdisciplinary collaborative design processinvolving material explorations, prototyping, first-person-perspective and user studies, can lead to the creation of a garment that invites various perceptual and emotional responses in its wearer. The article reflects on the design journey, highlighting the transdisciplinary team's research through design experience and shared language for knowledge exchange. This process has revealed new research paths for an emerging field of 'sensorial clothing', combining the various team members' fields of expertise and resulting in a wearable prototype.